ON THE COMPUTATION OF HIGH-DIMENSIONAL POTENTIALS OF ADVECTION–DIFFUSION OPERATORS. Issue 2 (24th February 2015) - Lanzara, Flavia; Schmidt, Gunther
Abstract : We study a fast method for computing potentials of advection–diffusion operators $-{\rmΔ}+2b\boldsymbol{· }{\rm\nabla}+c$ with $b\in \mathbb{C}^{n}$ and $c\in \mathbb{C}$ over rectangular boxes in $\mathbb{R}^{n}$ . By combining high-order cubature formulas with modern methods of structured tensor product approximations, we derive an approximation of the potentials which is accurate and provides approximation formulas of high order. The cubature formulas have been obtained by using the basis functions introduced in the theory of approximate approximations. The action of volume potentials on the basis functions allows one-dimensional integral representations with separable integrands, i.e. a product of functions depending on only one of the variables. Then a separated representation of the density, combined with a suitable quadrature rule, leads to a tensor product representation of the integral operator. Since only one-dimensional operations are used, the resulting method is effective also in the high-dimensional case.